L’écriture au second degré de Jean Anouilh: l’exemple des personnages d’enfants - Matoušková, Jiřina (Verbum – Analecta Neolatina, 2019)
The paper deals with the analysis of intertextuality in the plays written by Jean Anouilh with the special focus on child characters, especially on the character of a revolting son. Inspired by one of the plays by Roger Vitrac, such a character makes its first appearance in Anouilh’s dramatic world in 1948. It later becomes a permanent feature in his works and thus it creates the archetype of a son. Using the terminology established by Gérard Genette, we first describe the parallels between Vitrac’s and Anouilh’s plays, then we analyse the methods of macrotextual transcription, on which Anouilh keeps on focusing until the end of his literary career. We also explore the transitions from one play to another and we argue that such a return in cycles is a key factor in understanding the coherence, aesthetics and legacy of Anouilh’s plays written since the beginning of 1960s.